Comparative Study of Direct and Cooperative Method of Teaching Financial Accounting in Federal Colleges of Education, North-East Geo-Political Zone, Nigeria. - Umar, Rahmat Talatu (NIU Journal of Social Sciences, 2017)
This study compared the effect of direct and cooperative teaching methods on students’ performance in Financial Accounting in federal colleges of education in north-east, Nigeria. Quasi experimental design was adopted for the study. Three research questions were raised to guide the study and Null hypotheses were formulated testing at 0.05 level of significance. The population of the selected students stood at 482 and the sample size was 162. Descriptive statistics in terms of mean and standard deviation were used in answering the three research questions raised while t-test statistics was used in testing the null hypotheses. The findings revealed that the academic performance of students taught with cooperative method is significant better than those taught with direct Teaching Method in Federal Colleges of Education in North-East, Nigeria. It was concluded that students can improve their critical thinking and intellectual skills by learning from one another. It was therefore recommended that cooperative teaching method should be encouraged generally in teaching and learning process, in order to improve the level of academic performance of students especially in Accounting and other subjects of studies. Keywords: Direct Teaching, Cooperative Teaching, Academic Performance, Financial Accounting